Ann Radcliffe's The Mysteries of Udolpho and Jane Austen's Northanger Abbey: A Comparison of the Two Novels - Šimáková, Iva (Univerzita Pardubice, 2011)
The aim of this thesis is to show the elements of a parody of the Gothic genre in Jane Austen's novel, in contrast to the work of Ann Radcliffe. The first part focuses on characterizing the Gothic genre. It also gives description of origin, features and development of this genre, from its beginning to its end, in England. The second part of the paper describes lives and works of both authoresses, Ann Radcliffe and Jane Austen. Radcliffe is considered one of the most important authors of the Gothic fiction. Jane Austen, who was also influenced by the genre, however, wrote its parody. The last part of the thesis focuses on analysis of Austen's novel Northanger Abbey and compares it with Radcliffe's work The Mysteries of Udolpho. The thesis will conclude by providing an explanation where Northanger Abbey's parody lies, in comparison with one of the most typical example of the Gothic genre.
Srovnání románů Tajemství Udolpha Ann Radcliffeové a Northangerské opatství Jane Austenové
Keywords: Radcliffe, Ann; Austen, Jane; gotický román; osmnácté století; devatenácté století; Záhady Udolpha; Northangerské opatství; Northanger Abbey; Radcliffe, Ann; Austen, Jane; Gothic novel; eighteenth century; nineteenth century; Mysteries of Udolpho